Penerapan Metode Promethee dalam Menentukan Wilayah Dengan Tingkat Kelesuhan Uang Rupiah Di Kantor Perwakilan Bank Indonesia Pematangsiantar - Dermawan, Sabaruddin; Damanik, Irfan Sudahri; Saragih, Ilham Syahputra (STIKOM Tunas Bangsa Pematangsiantar, 2021)
The Promethee method belongs to the Multi Criteria Decision Making (MCDM) problem solving group which is a very important scientific discipline in decision making or a problem that has more than one criterion (multi criteria). The main objective of the PROMETHEE approach is to facilitate the decision making process by grouping decision types into 6 criteria functions that can adequately represent all types of decisions to solve everyday cases and quantify the degree of preference by using a maximum of 2 parameters that have economic characteristics significant To avoid the element of subjectivity in determining money riots, the authors try to implement a decision support system contained in PROMETHEE that is able to assist in determining the level of money riots. Decision support system is an interactive system that supports the decision making process (Kurniawan, 2015). PROMETHEE method is one method that uses the principle of outranking to solve the problem of decision making to determine the best alternative from a number of alternatives based on established criteria.